Design and on-field test of ESPAR antenna for UAV-based long-range IoT applications - Positano, Francesco; Lizzi, Leonardo; Staraj, Robert (Frontiers in Antennas and Propagation, 2024)
The Internet of things is increasingly focused on UAV-based long-range applications. This necessitates versatile, low-cost antenna designs for both ground stations and drones. This study proposes the design of a pattern reconfigurable parasitic element antenna system operating in the LoRa 868 MHz band and its on-field characterization. The electronic steerable parasitic array radiator (ESPAR) antenna consists of a single-fed shorted patch surrounded by four rectangular parasitic elements. The antenna system can develop four directive beams, each activated by one of four PIN diodes, and an omnidirectional pattern obtained when all diodes are turned off. The antenna has been characterized both in an anechoic controlled environment and in a practical on-field drone-to-ground packet transmission scenario. Results based on received signal strength indicator (RSSI) show that the pattern reconfigurability becomes increasingly relevant with the end-point distance and that pointing the beam at the end point always allows the highest RSSI level to be received.